Internal carotid artery dissection associated with acute dengue virus infection: a case report - Higa Lee, Annelise Akemi (2024)
Cervical artery dissections (CAD) can occur spontaneously or as a direct result of significant trauma. Viral infections, such as SARS-CoV2, influenza, and Epstein Barr, are risk factors for spontaneous CAD. Dengue virus infections have dramatically increased in recent decades, and Brazil is one of the endemic areas. The dengue virus can cause headache and neurological complications such as encephalitis, myelitis, Guillain-Barré syndrome, and myositis. No report has yet been found in the literature of dissection of the internal carotid artery secondary to dengue infection. Our objective is to report the case of a patient with dissection of the internal carotid artery associated with acute dengue virus infection.